Comparative analysis of conventional vs high-resolution anorectal manometry methods - Silvana Marques e Silva; Marcelo de Melo Andrade Coura; Romulo Medeiros de Almeida; Isabel Ferreira Saenger; Valéria Cardoso Pinto; João Batista de Sousa (PLoS ONE, 2025)
Introduction High-resolution anorectal manometry (HR-ARM) is gradually replacing conventional anorectal manometry (C-ARM). Despite reports of a strong correlation between the two methods in pressure measurements, normative values vary significantly across different devices. This study, therefore, compares manometric parameters between C-ARM and HR-ARM performed in the same individuals. Materials and methods Fifty consecutive symptomatic patients requiring anorectal manometry, irrespective of their primary complaint, underwent both C-ARM and HR-ARM performed by the same examiner. Agreement between the two methods was assessed based on the type of variable: the intraclass correlation coefficient was used for continuous parameters, while simple or weighted Kappa coefficients were used for categorical parameters. Results The study cohort (n = 50) had a mean age of 58.06 years, and 78% were female. For continuous variables, agreement between C-ARM and HR-ARM was excellent for resting and squeeze pressures but poor for functional anal canal length. When these pressures were categorized based on each method’s normative values, the diagnostic agreement for anal tone was only fair to moderate. Regarding specific disorders, the agreement for dyssynergia markers was moderate. However, it was only fair for rectal relaxation and poor for intra-rectal propulsion. Conclusions C-ARM and HR-ARM show excellent agreement for the quantitative assessment of resting and squeeze pressures. However, when these pressures are categorized using currently available normative values, the diagnostic agreement between the methods is poor. This strongly suggests that unique, device-specific reference ranges must be established to ensure accurate clinical interpretation.